Designbuild education - Kraus, Chad (New York ; Abingdon, Oxon : Routledge, Taylor & Francis Group, 2017)
Designbuild Education adopts the intellectual framework of American Pragmatism, which is a theory of action, to investigate architects' compelling urge to build and how that manifests in collegiate designbuild programs. Organized into four themes-people, poetics, process, and practice-the book brings together new essays by some of today's most well-known designbuild educators, including Andrew Freear from Rural Studio and Dan Rockhill from Studio 804, to shed light on the theoretical dimensions of their practice and work. Illustrated with over 100 black and white images.
People : community engagement and the common good --
Poetics : experience and the human condition --
Process : methodology and the tectonic imagination --
Practice : the academic-professional bridge.
Includes bibliographical references (pages 231-235) and index.
ARC
Trim Education
Keywords: Architecture -- Study and teaching; Architects -- Training of; Architecture